Effects of bushen huoxue method for knee osteoarthritis: A protocol for systematic review and meta-analysis. Issue 24 (12th June 2020) - Chen, Guocai; Ye, Xiangling; Guan, Yingxin; Liu, Wengang; Du, Jianping; Yao, Nan; Xu, Xuemeng
Abstract: Background: Knee osteoarthritis (KOA) is a common progressive joint disorder in old people. Bushen huoxue (BSHX) is a classical method of TCM in treating KOA. However, there is no systematic review related to BSHX for KOA. The purpose of this study is to provide a comprehensive and reliable evaluation of the clinical evidence of BSHX in the treatment of KOA. Methods: We searched relevant studies on BSHX for KOA from the databases of PubMed, Embase, MEDLINE, Cochrane Library Central Register of Controlled Trials, China national knowledge infrastructure database (CNKI), Wan fang database, Chongqing VIP information, and SinoMed from their inception to May 2020. Two researchers will select and evaluate qualified studies independently. The primary outcomes of this review will focus on pain intensity. The meta-analyses will be performed by using the RevMan 5.3. Results: The study will provide a comprehensive evaluation of the efficacy and safety of the BSHX method for patients with KOA. Conclusion: The results of this systematic review will provide evidence to judge whether BSHX is an effective intervention for patients with KOA.